2019
DOI: 10.1186/s13018-019-1120-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of patients with extremity myxoid liposarcomas after surgery

Abstract: Background Extremity myxoid liposarcoma (MLS) is a rare soft tissue sarcoma in adults. We performed this study to define distinctive clinical features of extremity MLS by assessing prognostic factors. Methods Between 1973 and 2015, 1756 patients with extremity MLS who underwent surgical resection were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database of the US National Cancer Institute. Both overall survival (OS) and cancer-specific survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 22 publications
5
31
2
1
Order By: Relevance
“…Previous studies have identified large tumor size as an indicator of poor prognosis for extremity STS patients [3,10,13,14,22], consistent with the present research. This is probably because a large tumor size is related to higher biologic malignancy, including regional invasiveness and metastatic potential.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have identified large tumor size as an indicator of poor prognosis for extremity STS patients [3,10,13,14,22], consistent with the present research. This is probably because a large tumor size is related to higher biologic malignancy, including regional invasiveness and metastatic potential.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, the American Joint Committee on Cancer (AJCC) system, known as the TNM staging system, remains the gold standard for prognostic prediction for tumor patients. However, other elements that have been reported to be prognostic factors for extremity STS patients are not taken into consideration in the TNM staging system, such as patient factors (including age and sex), tumor characteristics (including tumor grade, histologic subtype, and tumor location), and treatment strategies (including surgery, radiotherapy, and chemotherapy) [7,[9][10][11][12][13][14][15]. More importantly, the TNM staging system is unable to meet the increasing need for precision medicine and cannot provide individual predictions of prognosis at specific times [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Potentially due to the application of the present statistical model, interesting results emerged: Female gender was independently associated with a significantly lower risk of LR and DM. An association between gender and overall survival (OS) has been observed by Maretty-Nielsen et al and Wu et al [2,23]. However, an association between gender and LR-free as well as DM-free survival has not been described thus far [24].…”
Section: Discussionmentioning
confidence: 96%
“…Smith et al showed no sex differences among well-differentiated liposarcoma in the overall and disease-specific survival [11]. However, another study that examined survival among patients with extremity myxoid liposarcomas, showed males as being a negative survival predictor [9]. For all cancer types overall, the increased cancer risk and poor survival among males has been established by population-based data [27][28][29].…”
Section: Discussionmentioning
confidence: 99%